Longevity and Biodegradability Assessment of Biobased Lighting Fixture Design for Interiors - Turhan-Haskara, Gozde Damla (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Biobased materials are often associated with fast degradation due to their inherent biodegradability, limiting their adoption in long-term applications. This study explores the dual potential of biobased composites, particularly bacterial cellulose-based materials, through the case of lighting fixture design in interior spaces. While these materials naturally degrade under specific environmental conditions, their lifespan can be extended significantly through thoughtful design and controlled usage. The research involves a four stage methodology to focus on developing and testing composite materials by combining bacterial cellulose biofilms with various biobased agents to enhance light transmission and durability. The study then evaluates the performance of these composites in terms of illuminance quality and biodegradation in interior use and composting, comparing them to one of the conventional lighting fixture materials, polypropylene plastic. The results have shown that this study challenges the perception of biobased materials as inherently fast-degrading due to maintenance requirements, by demonstrating their capacity for longevity when utilized in stable indoor environments. The findings contribute to biodesign discourse by showcasing how biobased composites can balance biodegradability and extended usability, offering innovative pathways for a variety of ecological design applications.